System and method for preparing formic acid through CO2RR
By using alkali metal cations in the acid proton exchange membrane system to regulate the electrode interface characteristics and intermittent new energy power generation, combined with bismuth-based catalysts and carbon materials, the problems of low formic acid conversion and carbonate deposition in the CO2RR formic acid system are solved, efficient generation of formic acid and energy recovery are achieved, and the carbon utilization rate of the system and the self-repair ability of the electrode are improved.
Patent Information
- Application Number
- CN202510625382.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-07-18
AI Technical Summary
In the existing CO2RR formic acid system, the conversion rate of formic acid is low, the energy consumption is high, the carbonate deposition and product losses are serious, the target product efficiency is low under alkaline electrolytes, the loss caused by anion migration and the overpotential of oxygen evolution reaction are increased.
The acidic proton exchange membrane system is adopted to regulate the electrode interface characteristics through alkali metal cations, inhibit hydrogen evolution reaction, optimize the distribution of CO2RR intermediates, combine intermittent new energy power generation, dissolve carbonate with an acidic environment, realize self-healing of GDE, and enhance the electrode performance using bismuth-based catalysts and carbon materials.
It improves carbon utilization, reduces formate formation and carbonate deposition, achieves efficient resource utilization and energy recovery, enhances the mechanical properties and reaction efficiency of the electrode, and realizes zero emissions of CO2 and efficient recycling of products.
Smart Images

Figure CN120330734A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a CO2RR formic acid production system and method. Background Art
[0002] In recent years, CO2 electrochemical reduction (CO2RR) has received extensive attention because it can produce a variety of products, including formic acid, carbon monoxide (CO), and chemical products and fuels containing two or more carbon atoms, using renewable electricity under ambient pressure and mild temperature conditions. Among them, formic acid is regarded as an attractive and versatile product due to its relatively high market price, wide applications (such as leather tanning, rubber coagulation, pharmaceutical industry), and potential in the fields of biotechnology and energy storage.
[0003] Gas diffusion electrodes (GDEs) play a key role in CO2RR. Through their porous and partially wetted structures, they promote close contact between gas, solid, and liquid, enhance the mass transfer of gas CO2 to the surface of the electrocatalyst, and thus improve the current efficiency of the reduction products.
[0004] During the process of reducing CO2 to formic acid, the electrocatalytic reaction occurring on the cathode side is as follows:
[0005] CO2 + H2O + 2e - →HCOO - + OH - (1)
[0006] CO2 + H2O + 2e - →CO + 2OH - (2)
[0007] 2H2O + 2e - →H2 + 2OH - (3)
[0008] CO2RR usually uses alkaline electrolytes because under neutral or acidic conditions, the cathode is more likely to undergo the hydrogen evolution side reaction, resulting in a very low current efficiency (FE value) of the target product. However, there are still a series of challenges in using alkaline electrolytes in industrial applications: (1) Under alkaline conditions, CO2RR mainly produces formate, which needs to be further acidified to convert into the actual required formic acid product. This process is not only costly but also has prominent environmental problems; (2) CO2 reacts with OH - generated at the cathode to form a "trap state", leading to the accumulation of (bi)carbonate; the carbonate may not only precipitate in the GDE, blocking the pores of the GDE and thus blocking the path of CO2 diffusion to the catalyst surface, but also cause uneven volume expansion, resulting in the deterioration of the GDE structure; (3) When using alkaline electrolytes, an anion exchange membrane (AEM) is usually selected, and the anionic reduction products (such as CO32- , OH - ) migrates to the anode side through the exchange membrane, which will increase the overpotential of the oxygen evolution reaction (OER), resulting in the loss of target products. Summary of the Invention
[0009] The technical problem to be solved by the present invention is to overcome the defects of low formic acid conversion rate and high energy consumption in the existing technology for formic acid production by CO2RR, and to provide a CO2RR system and method for formic acid production. The CO2RR system for formic acid production of the present invention can not only efficiently generate formic acid, reduce the formation of formate salts, avoid carbonate deposition and product loss, and greatly improve the carbon utilization rate; but also can achieve efficient resource utilization and energy recovery. In addition, the system cleverly utilizes the intermittency of new energy power generation, dissolves carbonate precipitates in an acidic environment, realizes self-repair of the GDE, and restores electrochemical activity.
[0010] The present invention solves the above technical problems through the following technical solutions.
[0011] The present invention provides a CO2RR system for formic acid production, which includes: a CO2RR electrolytic cell, a gas-liquid separator and a burner; wherein, the CO2RR electrolytic cell includes an anode chamber, a cation exchange membrane and a cathode chamber; the gas-liquid separator is communicated with the cathode chamber for receiving electrolysis products; the gas-liquid separator is communicated with the burner and is used for supplying gas to the burner; the anode chamber is communicated with the burner and is used for supplying gas to the burner; the burner is communicated with the cathode chamber and is used for supplying CO2 to the cathode chamber;
[0012] The anode chamber is internally provided with an anode electrode and an anode electrolyte, and the anode electrolyte provides H for the cathode chamber through the cation exchange membrane + .
[0013] Through research, in the acidic medium of the proton exchange membrane (CEM) diaphragm system, the introduction of alkali metal cations can inhibit the hydrogen evolution reaction (HER) by regulating the electrode interface characteristics, and its mechanism of action includes: ① Alkali metal cations form an electric field shielding layer in the outer Helmholtz plane, reducing the migration driving force of anions; ② Hindering the diffusion of hydronium ions to the electrode surface and inhibiting the HER kinetic process; ③ Optimizing and stabilizing the key intermediates of CO2RR through the electric double layer electric field distribution, thereby improving the selectivity of target products; ④ Inhibiting the cross-diffusion of anions in the acidic medium and improving the carbon efficiency of the system. The above mechanism provides a theoretical basis for the feasibility of CO2RR in the acidic system.
[0014] In the present invention, the energy source of the CO2RR electrolytic cell can be an intermittent power supply energy source. The energy source of the CO2RR electrolytic cell can adopt new energy power generation.
[0015] In the present invention, the CO2RR electrolyzer may adopt an MEA electrolyzer. The MEA electrolyzer can simulate the characteristics of intermittent power supply of new energy power generation.
[0016] In the present invention, the CO2RR formic acid production system may further include an anodic electrolyte storage tank, and the anodic electrolyte storage tank is communicated with the anodic chamber.
[0017] In the present invention, in the anodic electrode, the anodic catalyst may adopt a metal or metal oxide effective for OER, such as one or more of a platinum-based catalyst, an iridium-based catalyst, and a ruthenium-based catalyst, and preferably a platinum-carbon catalyst.
[0018] Preferably, if the anodic catalyst is a supported net, fiber, or foam structure, it can be directly cleaned and used as an OER electrode; if the anodic catalyst is in powder form, it needs to be prepared into an electrode.
[0019] In the present invention, the anodic electrode may adopt a titanium mesh electrode plated with iridium oxide or a gas diffusion electrode anode.
[0020] Among them, preferably, when the anodic electrode adopts a gas diffusion electrode anode, the gas diffusion electrode anode may adopt a titanium felt or a porous titanium plate.
[0021] In the present invention, the anodic electrolyte may be a K2SO4 solution and / or an H2SO4 solution.
[0022] Among them, the concentration of the K2SO4 solution may be 0.1 - 0.5 mol / L, such as 0.3 mol / L.
[0023] Among them, when the anodic electrolyte is a mixed solution of K2SO4 and H2SO4, the pH value may be 1 - 3, such as a pH value of 1.
[0024] In the present invention, preferably, a gas concentration sensor is provided on the pipeline connecting the anodic chamber and the burner.
[0025] In the present invention, the cation exchange membrane may be a perfluorosulfonic acid-based polymer membrane, preferably a Nafion117 membrane. Preferably, the Nafion 117 membrane is activated in a 1M HCl solution before use.
[0026] In the present invention, the CO2RR formic acid production system may further include a CO2 gas storage tank, and the CO2 gas storage tank is communicated with the cathodic chamber.
[0027] Preferably, a humidifier is further provided on the pipeline connecting the CO2 gas storage tank and the cathode chamber. Through the humidifier, CO2 can be used as a reaction raw material in the form of water-saturated gaseous CO2. In order to optimize the separation effect of gas sampling and liquid product sampling in the present invention, the cathode electrolyte solution design is not adopted in the cathode region. The reaction activity of CO2 is enhanced by increasing its humidity.
[0028] Preferably, the electrolytic cell adopts a zero-gap CO2RR electrolytic cell.
[0029] In the present invention, in the cathode chamber, the effective area of the cathode electrode can be 2-8 cm 2 , for example, 4 cm 2 .
[0030] In the present invention, in the cathode chamber, the loading amount of the cathode catalyst in the cathode electrode can be 2-8 mg, for example, 4 mg.
[0031] In the present invention, in the cathode chamber, the cathode electrode can be prepared by the following method: stirring and heating, hot pressing treatment and shaping treatment are carried out on a mixture containing a cathode catalyst, a conductive agent and polytetrafluoroethylene to obtain an electrode membrane; the electrode membrane is covered on the cathode gas diffusion layer and hot pressed for the second time to obtain the cathode electrode.
[0032] Among them, the cathode catalyst can be a bismuth catalyst. The bismuth catalyst is preferably one or more of bismuth metal, bismuth oxide and bismuth halide; more preferably, the bismuth catalyst further includes one or more of carbon materials, metals and metal oxides.
[0033] The carbon material is preferably one or more of carbon particles, carbon fibers, carbon nanotubes, carbon nanowires, single-layer graphene oxide, single-layer reduced graphene, multi-layer graphene oxide, multi-layer reduced graphene and porous carbon black.
[0034] The metal in the metal or the metal oxide is preferably one or more of potassium, titanium, vanadium, manganese, cobalt, nickel, copper, zinc and indium.
[0035] Preferably, the bismuth catalyst is α-phase and / or β-phase; for example, one or more of α-Bi2O3, BiOCl, β-Bi2O3@BiOCl and β-Bi2O3@In2O3@rGO.
[0036] The α-Bi2O3 can be prepared by the following method a: mixing a bismuth source solution A and polyvinylpyrrolidone, adjusting the pH to alkaline, drying and calcining to obtain α-Bi2O3.
[0037] The β-Bi2O3@In2O3@RGO can be prepared by the following method b: Mix the bismuth source solution B, reduced graphene oxide, indium nitrate, and polyvinylpyrrolidone, adjust the pH to alkaline, dry, and calcine to obtain β-Bi2O3@In2O3@RGO.
[0038] The BiOCl or β-Bi2O3@BiOCl can be prepared by the following method c: Under heating conditions, drop the bismuth source solution C into the mixed solution containing potassium chloride and polyvinylpyrrolidone for reaction to obtain BiOCl or β-Bi2O3@BiOCl.
[0039] In the bismuth source solution A, bismuth source solution B, or bismuth source solution C, the bismuth source can be selected from bismuth nitrate.
[0040] In method a, in the bismuth source solution A, the solvent can be selected from nitric acid. The concentration of the nitric acid is preferably 1 mol / L.
[0041] In method a, in the bismuth source solution A, the concentration of bismuth element can be 0.05 - 0.2 mol / L, such as 0.1 mol / L.
[0042] In method a, the molar ratio of the bismuth source to the polyvinylpyrrolidone in the bismuth source solution A can be 1:(1 - 5), such as 1:2.
[0043] In method a or method b, preferably, the pH is adjusted to a pH value of 7.5 - 9.5, such as 8 or 9.
[0044] In method a or method b, after adjusting the pH and before drying, a washing step can also be included.
[0045] In method a or method b, the drying temperature can be 70 - 90 °C, such as 80 °C.
[0046] In method a or method b, the drying time can be 1 - 3 h, such as 2 h.
[0047] In method a, the calcination temperature can be 200 - 400 °C, such as 300 °C.
[0048] In method a, the calcination time can be 5 - 8 h, such as 6 h.
[0049] In method a, preferably, the diameter of the α-Bi2O3 is 50 - 300 nm and the thickness is 25 - 35 nm.
[0050] In method b, in the bismuth source solution B, the solvent can be selected from ethylene glycol and / or ethanol. Preferably, the solvent is ethylene glycol and ethanol, and the volume ratio of ethylene glycol to ethanol is 1:(0.5 - 2), such as 1:1.
[0051] In method b, in the bismuth source solution B, the concentration of bismuth element can be 0.03 - 0.06 mol / L, such as 0.045 mol / L.
[0052] In method b, the mass ratio of the bismuth source to the reduced graphene oxide in the bismuth source solution B can be (400 - 500):1, such as 436.5:1.
[0053] In method b, the molar ratio of the bismuth source to indium nitrate in the bismuth source solution B can be (5 - 15):1, such as 9:1.
[0054] In method b, the molar ratio of the bismuth source to polyvinylpyrrolidone in the bismuth source solution B can be 1:(1 - 5), such as 1:2.2.
[0055] In method b, the calcination temperature can be 500 - 700 °C, such as 600 °C.
[0056] In method b, the calcination time can be 5 - 7 h, such as 6 h.
[0057] In method b, the calcination can be carried out in an inert atmosphere. The inert atmosphere is preferably nitrogen.
[0058] In method b, preferably, the diameter of the β - Bi2O3@In2O3@rGO is 300 - 500 nm.
[0059] In method c, the temperature of the heating condition can be 70 - 90 °C, such as 80 °C.
[0060] In method c, in the bismuth source solution C, the solvent can be selected from ethylene glycol.
[0061] In method c, in the bismuth source solution C, the concentration of bismuth element can be 0.05 - 0.2 mol / L, such as 0.1 mol / L.
[0062] In method c, the molar ratio of the bismuth source to potassium chloride in the bismuth source solution C can be 1:(0.2 - 5).
[0063] Preferably, when preparing β - Bi2O3@BiOCl, the molar ratio of the bismuth source to potassium chloride in the bismuth source solution C is 1:(0.2 - 1) and not 1:1, such as 1:0.4.
[0064] Preferably, when preparing BiOCl, the molar ratio of the bismuth source to potassium chloride in the bismuth source solution C is 1:(1 - 5), such as 1:2.
[0065] In method c, the molar ratio of the bismuth source to polyvinylpyrrolidone in the bismuth source solution C can be 1:(1 - 5), such as 1:2.
[0066] In Method c, the reaction time can be 0.5 - 1.5 h, such as 1 h.
[0067] In Method c, after the reaction, it may further include the steps of washing and / or drying.
[0068] In Method c, preferably, the diameter of the BiOCl is 300 - 500 nm and the thickness is 30 - 50 nm.
[0069] In Method c, preferably, the diameter of the β - Bi2O3@BiOCl is 300 - 500 nm and the thickness is 30 - 50 nm.
[0070] Among them, the conductive agent can be selected from carbon black;
[0071] Among them, the mixture may further include a solvent. The solvent is preferably an aqueous solution of isopropanol.
[0072] Among them, preferably, the mixture is prepared by first stirring the raw materials in an ice - water bath once and then stirring them at room temperature a second time.
[0073] The rotation speed of the first - stage stirring and the second - stage stirring can independently be 1000 - 3000 rpm, such as 2000 rpm.
[0074] The time of the first - stage stirring can be 20 - 40 min, such as 30 min.
[0075] The time of the second - stage stirring can be 0.5 - 1.5 h, such as 1 h.
[0076] Among them, the heat - preservation temperature of the stirring and heating can be 80 - 90 °C, such as 85 °C.
[0077] Among them, the stirring speed of the stirring and heating can be 2000 - 4000 rpm, such as 2000 rpm or 3000 rpm.
[0078] Among them, the stirring time of the stirring and heating can be 0.5 - 1.5 h, such as 1 h.
[0079] Among them, the temperature of the hot - pressing treatment can be 70 - 90 °C, such as 80 °C.
[0080] Among them, the pressure of the hot - pressing treatment can be 1.5 - 3 ton, such as 2 ton.
[0081] Among them, the time of the hot - pressing treatment can be 5 - 15 min, such as 10 min.
[0082] Among them, after the hot - pressing treatment, the thickness of the material can be 0.5 - 1.5 mm, such as 1.0 mm.
[0083] Among them, after the shaping process, the thickness of the electrode film can be 200 - 400 μm, such as 300 μm.
[0084] Among them, the shaping process can adopt the method of thinning by a rolling press. Preferably, the method of gradual thinning is adopted, and drying is carried out after each thinning; for example, first thin to 500 μm, then thin to 300 μm, and heat at 80 °C for 15 min after each thinning.
[0085] Among them, the temperature of the secondary hot pressing can be 80 - 150 °C, such as 100 °C.
[0086] Among them, the pressure of the secondary hot pressing can be 0.1 - 2 ton, such as 2 ton.
[0087] Among them, the time of the secondary hot pressing can be 10 - 60 min, such as 30 min.
[0088] Among them, the cathode gas diffusion layer can be selected from carbon cloth.
[0089] The carbon cloth can be prepared by the following method: dispersing acidified carbon nanotubes and / or graphene in a solvent to obtain a suspension; subjecting the suspension to vacuum filtration and drying to obtain the carbon cloth.
[0090] The thickness of the carbon cloth can be 300 - 500 μm, such as 400 μm.
[0091] The suspension can also include reduced graphene oxide. The mass ratio of the acidified carbon nanotubes to the reduced graphene oxide is preferably (3 - 5):1, such as 4:1.
[0092] The vacuum filtration can adopt the method of single - stage vacuum filtration or multi - stage vacuum filtration. Preferably, the multi - stage vacuum filtration adopts the following method: performing single - stage vacuum filtration on the suspension to obtain a carbon cloth base layer; impregnating the carbon cloth base layer with PTFE emulsion and performing secondary vacuum filtration; then drying to obtain the carbon cloth.
[0093] In the present invention, preferably, a gas concentration sensor is provided on the pipeline connecting the gas - liquid separator and the burner. In the present invention, the mixing ratio is monitored and controlled in real time by the gas concentration sensor to ensure that oxygen in the anode gas and CO and H2 in the cathode gas are mixed according to the stoichiometric ratio, and the supply amount of anode oxygen does not exceed the total reduction equivalent of the cathode gas, preventing unreacted residual oxygen from circulating into the cathode chamber.
[0094] In the present invention, the heat generated by the burner can supply heat to the CO2RR electrolytic cell to provide an appropriate electrolysis reaction temperature.
[0095] The present invention also provides a method for preparing formic acid, which is prepared by using the above-mentioned CO2RR formic acid preparation system.
[0096] In the present invention, preferably, a discontinuous electrolysis control method is used to apply current to the CO2RR formic acid preparation system, and the discontinuous electrolysis control method is to set a power-off time during continuous operation.
[0097] Among them, the discontinuous electrolysis control method can be to cut off the power after continuous operation for 1-5 h, such as 2 h or 4 h.
[0098] Among them, the power-off time for each time of the discontinuous electrolysis control method can be 15-45 min, such as 20 min or 30 min;
[0099] Among them, the current value of the applied current can be 150-250 mA / cm 2 , such as 200 mA / cm 2 .
[0100] Among them, the discontinuous electrolysis control method can be to cut off the power for 15-45 min after continuous operation for 1-5 h. Preferably, the power is cut off for 20 min after continuous operation for 2 h, or the power is cut off for 30 min after continuous operation for 4 h.
[0101] In the present invention, preferably, the flow rate of the anolyte flowing into the anode chamber is 0.5-1 mL·min -1 , such as 0.85 mL·min -1 .
[0102] In the present invention, preferably, the flow rate of CO2 in the CO2 gas storage tank introduced into the cathode chamber is 100-300 mL·min -1 , such as 200 mL·min -1 .
[0103] In the present invention, preferably, the discontinuous electrolysis control method is used to apply current to the CO2RR formic acid preparation system;
[0104] When applying current, the anolyte provides H through the cation exchange membrane for the cathode chamber + ; gaseous CO2 is introduced into the cathode chamber, and under the catalytic action of the cathode catalyst, the electrolysis reaction generates products formic acid, CO, H2 and unreacted CO2. After the products formic acid, CO, H2 and unreacted CO2 enter the gas-liquid separator for separation, the separated liquid is formic acid; the gas is CO, H2 and unreacted CO2, and after separation, it enters the burner; meanwhile, O2 is produced in the anode chamber and enters the burner; CO, H2 and O2 burn in the burner, and the generated CO2 and H2O are recycled to the cathode chamber for use as raw materials.
[0105] On the basis of conforming to the common knowledge in the art, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred examples of the present invention.
[0106] The reagents and raw materials used in the present invention are all commercially available.
[0107] The positive and progressive effects of the present invention are as follows:
[0108] The CO2RR formic acid production system provided by the present invention can not only efficiently generate formic acid, reduce the formation of intermediate product formate, but also effectively avoid carbonate deposition and the loss caused by the diffusion of the target product (in anionic form) through the exchange membrane to the anode side, thus significantly improving the carbon utilization rate. In addition, other products O2, CO and H2 generated in this system further react in the burner to generate H2O and CO2; these combustion products are then re-introduced into the CO2RR electrolytic cell as raw materials for recycling, realizing the efficient recycling of resources and the effective recovery of energy, as well as zero CO2 emissions.
[0109] Furthermore, the present invention uses polytetrafluoroethylene as a binder and prepares the cathode electrode by a dry method, which not only enhances the mechanical properties of the electrode; but also forms a hydrophobic property with a good network structure, effectively suppressing the common liquid overflow problem of traditional electrodes, ensuring the smooth diffusion of CO2 to the cathode electrode and reacting with the catalyst, further improving the conversion rate of formic acid.
[0110] New energy power generation has the disadvantage of intermittency. The CO2RR formic acid production system provided by the present invention can skillfully convert this characteristic into an advantage and realize the "self-healing" of the GDE. Specifically, during the power-on period, H + is generated in the anode chamber and enters the cathode chamber through the cation exchange membrane to create an acidic environment; when the power is interrupted, the acidic environment fully eliminates the pH gradient on the surface of the cathode electrode, promoting the dissolution of the residual carbonate precipitate in the pores of the GDE, thereby restoring the electrochemical activity of the GDE. Brief Description of the Drawings
[0111] Figure 1 It is a schematic diagram of the CO2RR formic acid production system of Example 1.
[0112] Figure 2 It is a flowchart of the CO2RR formic acid production method of Example 1.
[0113] Description of the Reference Numerals in the Drawings:
[0114] CO2RR electrolytic cell 1
[0115] Cathode chamber 11
[0116] Cation exchange membrane 12
[0117] Anode chamber 13
[0118] Gas-liquid separator 2
[0119] Formic acid storage tank 3
[0120] Gas concentration sensor 14
[0121] Burner 5
[0122] CO2 storage tank 6
[0123] Humidifier 61
[0124] Anode electrolyte storage tank 7
[0125] Gas concentration sensor 28 Specific implementation mode
[0126] The present invention will be further described below by way of examples, but the present invention is not limited to the scope of the described examples. The experimental methods not specified in the following examples are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0127] In a specific embodiment of the present invention, a zero-gap CO2RR electrolyzer is adopted.
[0128] Example 1
[0129] A CO2RR formic acid production system, which includes: a CO2RR electrolyzer 1, a gas-liquid separator 2 and a burner 5; wherein, the CO2RR electrolyzer 1 includes an anode chamber 11, a cation exchange membrane 12 and a cathode chamber 13; the gas-liquid separator 2 is communicated with the cathode chamber 13 for receiving electrolysis products; the gas-liquid separator 2 is communicated with the burner 5 and is used for supplying gas to the burner 5; the anode chamber 11 is communicated with the burner 5 and is used for supplying gas to the burner 5; the burner 5 is communicated with the cathode chamber 13 and is used for supplying CO2 to the cathode chamber 13; the anode chamber 11 is internally provided with an anode electrode and an anode electrolyte, and the anode electrolyte provides H for the cathode chamber 13 through the cation exchange membrane 12 + 。
[0130] The CO2RR formic acid production system is as Figure 1 shown, which includes a CO2RR electrolyzer 1, a gas-liquid separator 2 and a burner 5. Among them, the CO2RR electrolyzer includes an anode chamber 11, a cation exchange membrane 12 and a cathode chamber 13.
[0131] The inlet of the cathode chamber 13 is provided with a CO2 gas storage tank 6; a humidifier 61 is also provided between the CO2 gas storage tank 6 and the inlet of the cathode chamber 13, so that CO2 enters as water-saturated gaseous CO2 as a reaction raw material. The outlet of the cathode chamber 13 is connected to the inlet of the gas-liquid separator 2, and the outlet of the gas-liquid separator 2 is respectively connected to the inlet of the formic acid storage tank 3 and the burner 5; a gas concentration sensor 4 is also provided on the pipeline connecting the outlet of the gas-liquid separator 2 and the inlet of the burner 5, for controlling the volume number entering the burner 5. The inlet of the anode chamber 11 is provided with an anode electrolyte storage tank 7. The outlet of the anode chamber 11 is connected to the inlet of the burner 5; a gas concentration sensor 8 is also provided on the pipeline connecting the outlet of the anode chamber 11 and the inlet of the burner 5, for controlling the volume number entering the burner 5. The outlet of the burner 5 is connected to the inlet of the cathode chamber 13.
[0132] The cathode chamber 13 is internally provided with a cathode electrode and a cathode electrolyte, and the effective area of the cathode electrode is 4 cm 2 , and the loading amount of the cathode catalyst in the cathode electrode is 4 mg. During use, water-saturated gaseous CO2 is introduced into the cathode chamber 13 at a speed of 200 mL·min -1 , and an electrolysis reaction is carried out. Formic acid, CO, H2 and unreacted CO2 flow out of the cathode chamber 13 and enter the gas-liquid separator 2 for separation. The liquid is formic acid and enters the formic acid storage tank 3; the gas is CO, H2 and unreacted CO2, and enters the burner 5 through the gas concentration sensor 4.
[0133] The anode chamber 11 is internally provided with an anode electrode and an anode electrolyte. The anode electrode uses a platinum-carbon catalyst, and the anode electrolyte is a mixed solution of K2SO4 and H2SO4. The concentration of the K2SO4 solution is 0.3 mol / L, and the pH value of the mixed solution is 1. Nafion 117 membrane is used as the cation exchange membrane. The anode electrolyte flows into the anode chamber 11 from the anode electrolyte storage tank 7 at a flow rate of 0.85 mL·min -1 , and then provides H + for the cathode chamber 13 through the cation exchange membrane 12. After the electrolysis reaction, O2 is produced in the anode chamber 11 and enters the burner 5 through the gas concentration sensor 8.
[0134] The following reactions occur in the burner 5:
[0135] O2 + H2 → H2O
[0136] O2 + CO → CO2
[0137] The CO2 and H2O produced by the burner 5 are recycled to the cathode chamber 13 for use as raw materials. The heat generated by the burner 5 can heat the CO2RR electrolyzer 1 to provide an appropriate electrolysis reaction temperature and maintain the temperature of the inlet gas and the electrolysis reaction at 60 - 80 °C.
[0138] Among them, in this embodiment, the preparation method of the cathode electrode is as follows:
[0139] (1) Prepare bismuth catalyst:
[0140] Dissolve 1 mmol Bi2(NO3)3·5H2O (0.485 g) in 10 mL of 1 M HNO3 solution, add 2 mmol (0.222 g) of polyvinylpyrrolidone (PVP), stir until completely dissolved, and then continue to stir for 30 min to promote the uniform dispersion of the two. Under strong stirring, slowly add 1 M KOH solution to adjust the pH value of the reaction solution to 8, and then continue to stir for 30 min to promote sufficient precipitation. Centrifuge the above reactants, wash with deionized water to remove soluble substances in the precipitate, centrifuge again, wash repeatedly 3 times, and finally wash with anhydrous ethanol and centrifuge. Place the precipitate in a corundum crucible and dry at 80 °C for 2 h. Then transfer it to a muffle furnace and calcine at 300 °C for 6 h to obtain α-phase Bi2O3.
[0141] The product is nanosheets with a diameter of about 50 - 300 nm and a thickness of about 30 nm.
[0142] (2) Prepare carbon cloth:
[0143] Add 0.1 g of single-walled carbon nanotubes (length 5 - 30 μm, diameter 1 - 2 nm) to 20 mL of 2 M HNO3 solution, heat to 60 °C with stirring, and reflux for 2 h to remove residual metals in the carbon nanotubes and promote the hydrophilicity of the carbon nanotubes. After centrifuging the carbon nanotubes and repeatedly washing with water until neutral, add them to deionized water, disperse ultrasonically for 60 min to obtain a suspension of carbon nanotubes. Filter the above suspension under reduced pressure using a Buchner funnel with a diameter of 16 cm to obtain a carbon cloth layer composed of carbon nanotubes. After peeling it off from the filter membrane, dry it at 80 °C for 2 h.
[0144] The thickness of the carbon cloth is about 400 μm.
[0145] (3) Prepare the cathode electrode:
[0146] After mixing bismuth catalyst, carbon black, and PTFE (purchased from Daikin Japan, in powder form) evenly according to a mass ratio of 90:3:7, place the materials in a flask. First, place it in an ice-water bath and stir for 30 minutes. Stir the above materials with an electric stirrer at a speed of 2000 rpm. After maintaining for 1 hour, fully mix the above raw materials. Then place the flask in an electric heating mantle and heat the flask. The heating temperature is 85°C. Stir the above materials with an electric stirrer at a speed of 3000 rpm. After maintaining for 1 hour, quickly transfer the materials to a stainless-steel mold and perform hot-press treatment at 80°C and 2 tons of pressure for 10 minutes to press them into a sheet with a thickness of 1 mm. Then roll the electrode sheet while it is still hot on a rolling press into a film with a thickness of 500 μm. Heat the film in an oven at 80°C for 15 minutes and then roll it again with a rolling press into an electrode film with a thickness of 300 μm. Finally, cover the electrode film on the carbon cloth prepared in the above steps and perform hot-press treatment at 100°C and 1 ton of pressure for 30 minutes to press the two into one body.
[0147] The catalyst loading is determined by weighing the carbon cloth before and after hot pressing. In this example, the catalyst loading is 4 mg / cm 2 .
[0148] Among them, in this example, the preparation method of the anode electrode is as follows:
[0149] Fully mix 40 mg of commercial platinum-carbon catalyst (Maclean, platinum-carbon catalyst Pt 20%) with a mixed solution of 86 μL of Nafion solution (DuPont PFSA, 5 wt%, D520) and aqueous isopropanol solution (the volume percentage of isopropanol in the aqueous isopropanol solution is 1:1) to obtain catalyst ink; among them, the mass ratio of Nafion in the ink is 1 wt%, and the volume ratio of Nafion solution to aqueous isopropanol solution is 1:1. Use a porous titanium plate as the gas diffusion layer, and the electrode area is 4 cm 2 , and the catalyst loading is fixed at 1 mg cm -2 .
[0150] The flow chart of the CO2RR method for producing formic acid is as Figure 2 shown. When using the above CO2RR formic acid production system, apply a current of 200 mA / cm to the CO2RR electrolytic cell 1 through a potentiostat / galvanostat 2 .
[0151] During electrolysis, the anolyte flows into the anode chamber 11 from the anolyte storage tank 7 at a flow rate of 0.85 mL·min -1 , and then provides H for the cathode chamber 13 through the cation exchange membrane 12 + .
[0152] Gaseous CO2 is introduced from the CO2 gas storage tank 6 into the humidifier 61 to obtain water-saturated gaseous CO2, which is then introduced into the cathode chamber 13 at a rate of 200 mL·min -1 and, under the catalysis of the prepared catalyst α-phase Bi2O3, the electrolysis reaction produces formic acid, CO, H2, and unreacted CO2. After the products formic acid, CO, H2, and unreacted CO2 enter the gas-liquid separator 2 and are separated, the separated liquid is formic acid, which enters the formic acid storage tank 3 for storage; the gas is CO, H2, and unreacted CO2. After separation, it enters the burner 5 through the gas concentration sensor 4 (the gas concentration sensor is used to monitor and control the mixing ratio in real time to ensure that the oxygen in the anode gas and CO, H2 in the cathode gas are mixed according to the stoichiometric ratio, and the anode oxygen supply does not exceed the total reduction equivalent of the cathode gas to prevent unreacted residual oxygen from circulating into the cathode chamber 13). Meanwhile, O2 is produced in the anode chamber 11 and enters the burner 5 through the gas concentration sensor 8. CO, H2, and O2 burn in the burner 5, and the generated CO2 and H2O are recycled to the cathode chamber 13 for use as raw materials. The heat generated by the burner 5 can heat the CO2RR electrolyzer 1 to provide an appropriate electrolysis reaction temperature and maintain the inlet gas and electrolysis reaction temperature at 60 - 80 °C.
[0153] After 4 h of electrolysis, the current application is stopped. During the process of stopping the current application, the acidic environment in the cathode chamber can fully eliminate the pH gradient on the surface of the cathode electrode, promoting the dissolution of the residual carbonate precipitate in the pores of the GDE, thereby restoring the electrochemical activity of the GDE.
[0154] 30 min after stopping the current application, a current of 200 mA / cm 2 is applied again for electrolysis. The above "intermittent electrolysis control" is repeated three times. Before stopping the current application after each 4 h of electrolysis, 5 mL of the formic acid liquid separated by the gas-liquid separator 2 is collected for testing the Coulomb efficiency.
[0155] Example 2
[0156] Compared with Example 1, the only difference is the preparation of the bismuth catalyst. Specifically:
[0157] Dissolve 1 mmol Bi2(NO3)3·5H2O (0.485 g) in 10 mL of ethylene glycol. After stirring until completely dissolved, stir for another 30 min to promote the uniform dispersion of the two, which is solution A. Dissolve 2 mmol of KCl in 20 mL of water, then add 2 mmol (0.222 g) of PVP and stir to dissolve, which is solution B. Under strong stirring, heat solution B to 80 °C, slowly add solution A dropwise to solution B, and then continue stirring for 60 min to promote the full reaction and precipitation. Centrifuge the above reactants, wash with deionized water to remove soluble substances in the precipitate, centrifuge again, wash repeatedly 3 times, and finally wash with absolute ethanol and centrifuge. After treatment, dry at 80 °C for 2 h to obtain BiOCl.
[0158] The product is nanosheets with a diameter of about 300 - 500 nm and a thickness of about 30 - 50 nm.
[0159] Example 3
[0160] Compared with Example 1, the difference is only in the preparation of the bismuth catalyst. Specifically:
[0161] Dissolve 1 mmol Bi2(NO3)3·5H2O in 10 mL of ethylene glycol. After stirring until completely dissolved, stir for another 30 min to promote the uniform dispersion of the two, which is solution A. Dissolve 0.4 mmol of KCl in 20 mL of water, then add 2 mmol of PVP and stir to dissolve, which is solution B. Under strong stirring, heat solution B to 80 °C, slowly add solution A dropwise to solution B, and then continue stirring for 60 min to promote the full reaction and precipitation. Centrifuge the above reactants, wash with deionized water to remove soluble substances in the precipitate, centrifuge again, wash repeatedly 3 times, and finally wash with absolute ethanol and centrifuge. After treatment, dry in an oven at 80 °C for 2 h, and then place it in a vacuum drying oven at 180 °C for 6 h. Obtain β-Bi2O3@BiOCl composite catalyst, and the stoichiometric ratio of the two is 4:1.
[0162] The product is nanosheets with a diameter of about 300 - 500 nm and a thickness of about 30 - 50 nm.
[0163] Example 4
[0164] Compared with Example 1, the difference is only in the preparation of the bismuth catalyst. Specifically:
[0165] Bismuth catalyst: Dissolve 0.9 mmol of Bi2(NO3)3·5H2O in 10 mL of ethylene glycol, then add 10 mL of ethanol and 10 mg of reduced graphene oxide (rGO). After stirring evenly, ultrasonically disperse for 30 min, then add 0.1 mmol of In(NO3)3. After stirring until completely dissolved, add 2 mmol of polyvinylpyrrolidone (PVP). After stirring until completely dissolved, ultrasonically disperse again for 30 min to obtain Solution A. Under strong stirring, slowly add 1 M KOH solution to adjust the pH value of Solution A to 9, and then continuously stir for 30 min to promote full precipitation. Centrifuge the above reactants, wash with deionized water to remove residual soluble substances in the precipitate, centrifuge again, wash repeatedly 3 times, and finally wash with anhydrous ethanol and centrifuge. Place the precipitate in a corundum crucible and dry at 80 °C for 2 h. Then transfer it to a tubular furnace and calcine at 600 °C for 6 h under a nitrogen atmosphere to obtain the βBi2O3@In2O3@rGO composite catalyst.
[0166] The product is nanoparticles with a diameter of about 300 - 500 nm.
[0167] Example 5
[0168] Compared with Example 4, the only difference is the preparation of the carbon cloth. Specifically:
[0169] Add 0.08 g of single-walled carbon nanotubes (length 5 - 30 μm, diameter 1 - 2 nm) to 20 mL of 2 M HNO3 solution, heat to 60 °C with stirring, and reflux for 2 h to remove residual metals in the carbon nanotubes and promote the hydrophilicity of the carbon nanotubes. After centrifuging the carbon nanotubes and repeatedly washing with water until neutral, add them together with 0.02 g of rGO to 50 mL of deionized water. After ultrasonic dispersion for 60 min, obtain a suspension. Filter the above suspension under reduced pressure using a Buchner funnel with a diameter of 16 cm to obtain a carbon cloth layer composed of CNTs and rGO.
[0170] Dilute the PTFE emulsion (purchased from Daikin, Japan, 60% solid content) 10 times with deionized water, take 5 mL and add it to the above Buchner funnel. Immerse for 30 min first, then filter under reduced pressure to obtain the PTFE-modified carbon cloth. After peeling it off the filter membrane, place it on a polytetrafluoroethylene membrane and dry at 80 °C for 2 h.
[0171] The thickness of the carbon cloth is about 400 μm.
[0172] Effect Example
[0173] The cathode electrodes prepared in Examples 1-5 were made into MEA (membrane electrode) half-cells for electrochemical testing. Gold wires and silver / silver chloride electrodes (Ag / AgCl, 3M KCl, VWR, double-junction design) were used as the counter electrode (CE) and reference electrode (RE), respectively. Electrochemical measurements were completed using an Autolab (PGSTAT30) electrochemical workstation.
[0174] A potentiostat / galvanostat was used to apply a current of 200 mA / cm 2 to the MEA half-cell. After 4 h of electrolysis, the current application was stopped for 30 min, and then a current of 200 mA / cm 2 was applied again for electrolysis. The above "intermittent electrolysis control" was repeated three times. Before stopping the current application at 4 h for each electrolysis, 5 mL of formic acid liquid separated by the gas-liquid separator 2 was collected and tested for formic acid concentration using a high-performance liquid chromatograph, and was used for the calculation of the Coulombic efficiency.
[0175] The current efficiency of the target product is shown in Equation (1):
[0176]
[0177] Where:
[0178] i formic is the partial current (A)
[0179] i total is the total current (A)
[0180] C formic is the formic acid concentration (mg / L)
[0181] V is the volume of formic acid, 5 mL
[0182] F is the Faraday constant, 96485 C·mol -1
[0183] n is the number of electrons transferred
[0184] M is the molar mass of formic acid, 46.03 g / mol
[0185] t is the time, 1200 s
[0186] The test results are shown in Table 1 below.
[0187] Table 1
[0188]
[0189] As can be seen from the above table, Examples 1-5 of the present invention can all efficiently generate formic acid, and the conversion rate of formic acid is relatively high, reaching more than 44%.
[0190] Although the specific embodiments of the present invention have been described above, those skilled in the art should understand that this is only an example. The protection scope of the present invention is defined by the appended claims. Without departing from the principles and essence of the present invention, those skilled in the art can make various changes or modifications to these embodiments, but such changes and modifications all fall within the protection scope of the present invention.
Claims
1. A CO2RR formic acid production system, characterized in that, It includes: a CO2RR electrolyzer, a gas-liquid separator, and a burner; wherein, the CO2RR electrolyzer includes an anodic chamber, a cation exchange membrane, and a cathodic chamber; the gas-liquid separator is communicated with the cathodic chamber for receiving electrolysis products; the gas-liquid separator is communicated with the burner and is used for supplying gas to the burner; the anodic chamber is communicated with the burner and is used for supplying gas to the burner; the burner is communicated with the cathodic chamber and is used for supplying CO2 to the cathodic chamber; The anode chamber is internally provided with an anode electrode and an anode electrolyte, and the anode electrolyte provides H for the cathode chamber through the cation exchange membrane + .
2. The CO2RR formic acid production system according to claim 1, wherein The energy source of the CO2RR electrolyzer is an intermittent power supply energy source; and / or, the CO2RR formic acid production system further includes an anodic electrolyte storage tank, and the anodic electrolyte storage tank is communicated with the anodic chamber; and / or, in the anodic electrode, the anodic catalyst is one or more of a platinum-based catalyst, an iridium-based catalyst, and a ruthenium-based catalyst, preferably a platinum-carbon catalyst; and / or, the anodic electrode adopts an iridium oxide-coated titanium mesh electrode or a gas diffusion electrode anode; preferably, when the anodic electrode adopts a gas diffusion electrode anode, the gas diffusion layer adopts titanium felt or a porous titanium plate; and / or, the anodic electrolyte is a K2SO4 solution and / or an H2SO4 solution; preferably, the concentration of the K2SO4 solution is 0.1-0.5 mol / L, such as 0.3 mol / L; preferably, when the anodic electrolyte is a mixed solution of K2SO4 and H2SO4, the pH value is 1-3, such as the pH value is 1; and / or, a gas concentration sensor is provided on the pipeline where the anodic chamber is communicated with the burner; and / or, the cation exchange membrane is a perfluorosulfonic acid-based polymer membrane; preferably a Nafion 117 membrane; and / or, the CO2RR formic acid production system further includes a CO2 gas storage tank, and the CO2 gas storage tank is communicated with the cathodic chamber; preferably, a humidifier is further provided on the pipeline where the CO2 gas storage tank is communicated with the cathodic chamber; and / or, in the cathode chamber, the effective area of the cathode electrode is 2-8 cm 2 , such as 4 cm 2 ; and / or, in the cathodic chamber, the loading amount of the cathodic catalyst in the cathodic electrode is 2-8 mg, such as 4 mg; and / or, in the cathodic chamber, the cathodic electrode is prepared by the following method: stirring and heating a mixture containing a cathodic catalyst, a conductive agent, and polytetrafluoroethylene, performing hot pressing treatment and shaping treatment to obtain an electrode membrane; covering the electrode membrane on a cathodic gas diffusion layer and performing secondary hot pressing to obtain the cathodic electrode; and / or, a gas concentration sensor is provided on the pipeline where the gas-liquid separator is communicated with the burner; and / or, the heat generated by the burner supplies heat to the CO2RR electrolyzer.
3. The CO2RR formic acid production system according to claim 2, wherein The cathodic catalyst is a bismuth catalyst; the bismuth catalyst is preferably one or more of bismuth metal, bismuth oxide, and bismuth halide; more preferably, the bismuth catalyst further includes one or more of a carbon material, a metal, and a metal oxide; The carbon material is preferably one or more of carbon particles, carbon fibers, carbon nanotubes, carbon nanowires, single-layer graphene oxide, single-layer reduced graphene, multi-layer graphene oxide, multi-layer reduced graphene, and porous carbon black; The metal in the metal or the metal oxide is preferably one or more of potassium, titanium, vanadium, manganese, cobalt, nickel, copper, zinc, and indium; Further preferably, the bismuth catalyst is in the α-phase and / or β-phase; for example, one or more of α-Bi2O3, BiOCl, β-Bi2O3@BiOCl, and β-Bi2O3@In2O3@rGO; and / or, the conductive agent is selected from carbon black; and / or, the mixture further includes a solvent; the solvent is preferably an aqueous solution of isopropyl alcohol; and / or, the cathode gas diffusion layer is selected from carbon cloth.
4. The CO2RR formic acid production system according to claim 3, wherein, The bismuth catalyst is prepared by one or more of the following methods: Method a. Mix the bismuth source solution A and polyvinylpyrrolidone, adjust the pH to alkaline, dry, and calcine to obtain α-Bi2O3; Method b. Mix the bismuth source solution B, reduced graphene oxide, indium nitrate, and polyvinylpyrrolidone, adjust the pH to alkaline, dry, and calcine to obtain β-Bi2O3@In2O3@RGO; Method c. Under heating conditions, drop the bismuth source solution C into the mixed solution containing potassium chloride and polyvinylpyrrolidone for reaction to obtain BiOCl or β-Bi2O3@BiOCl.
5. The CO2RR formic acid production system according to claim 4, wherein In the bismuth source solution A, bismuth source solution B, or bismuth source solution C, the bismuth source is selected from bismuth nitrate; and / or, in Method a, in the bismuth source solution A, the solvent is selected from nitric acid; the concentration of the nitric acid is preferably 1 mol / L; and / or, in Method a, in the bismuth source solution A, the concentration of bismuth element is 0.05 - 0.2 mol / L, for example, 0.1 mol / L; and / or, in Method a, the molar ratio of the bismuth source to polyvinylpyrrolidone in the bismuth source solution A is 1:(1 - 5), for example, 1:2; and / or, in Method a or Method b, adjust the pH to a pH value of 7.5 - 9.5, for example, 8 or 9; and / or, in Method a or Method b, after adjusting the pH and before drying, a washing step is further included; and / or, in Method a or Method b, the drying temperature is 70 - 90 °C, for example, 80 °C; and / or, in Method a or Method b, the drying time is 1 - 3 h, for example, 2 h; and / or, in Method a, the calcination temperature is 200 - 400 °C, for example, 300 °C; and / or, in Method a, the calcination time is 5 - 8 h, for example, 6 h; and / or, in Method a, the diameter of the α-Bi2O3 is 50 - 300 nm and the thickness is 25 - 35 nm; and / or, in Method b, in the bismuth source solution B, the solvent is selected from ethylene glycol and / or ethanol; preferably, the solvent is ethylene glycol and ethanol, and the volume ratio of ethylene glycol to ethanol is 1:(0.5 - 2), for example, 1:1; and / or, in Method b, in the bismuth source solution B, the concentration of bismuth element is 0.03 - 0.06 mol / L, for example, 0.045 mol / L; and / or, in Method b, the mass ratio of the bismuth source to reduced graphene oxide in the bismuth source solution B is (400 - 500):1, for example, 436.5:1; and / or, in Method b, the molar ratio of the bismuth source to indium nitrate in the bismuth source solution B is (5 - 15):1, for example, 9:1; And / or, in method b, the molar ratio of the bismuth source in the bismuth source solution B to the polyvinylpyrrolidone is 1:(1 - 5), such as 1:2.2; And / or, in method b, the calcination temperature is 500 - 700 °C, such as 600 °C; And / or, in method b, the calcination time is 5 - 7 h, such as 6 h; And / or, in method b, the calcination is carried out in an inert atmosphere; the inert atmosphere is preferably nitrogen; And / or, in method b, the diameter of the β-Bi2O3@In2O3@rGO is 300 - 500 nm; And / or, in method c, the temperature of the heating condition is 70 - 90 °C, such as 80 °C; And / or, in method c, in the bismuth source solution C, the solvent is selected from ethylene glycol; And / or, in method c, in the bismuth source solution C, the concentration of bismuth element is 0.05 - 0.2 mol / L, such as 0.1 mol / L; And / or, in method c, the molar ratio of the bismuth source in the bismuth source solution C to the potassium chloride is 1:(0.2 - 5); preferably, when preparing β-Bi2O3@BiOCl, the molar ratio of the bismuth source in the bismuth source solution C to the potassium chloride is 1:(0.2 - 1) and not 1:1, such as 1:0.4; When preparing BiOCl, the molar ratio of the bismuth source in the bismuth source solution C to the potassium chloride is 1:(1 - 5), such as 1:2; And / or, in method c, the molar ratio of the bismuth source in the bismuth source solution C to the polyvinylpyrrolidone is 1:(1 - 5), such as 1:2; And / or, in method c, the reaction time is 0.5 - 1.5 h, such as 1 h; And / or, after the reaction in method c, it further includes the steps of washing and / or drying; And / or, in method c, the diameter of the BiOCl is 300 - 500 nm and the thickness is 30 - 50 nm; And / or, in method c, the diameter of the β-Bi2O3@BiOCl is 300 - 500 nm and the thickness is 30 - 50 nm.
6. The CO2RR formic acid production system according to claim 3, characterized in that, The carbon cloth is prepared by the following method: dispersing acidified carbon nanotubes and / or graphene in a solvent to obtain a suspension; subjecting the suspension to vacuum filtration and drying to obtain the carbon cloth; Preferably, the thickness of the carbon cloth is 300 - 500 μm, such as 400 μm; Preferably, the suspension further includes reduced graphene oxide; the mass ratio of the acidified carbon nanotubes to the reduced graphene oxide is preferably (3 - 5):1, such as 4:1; Preferably, the vacuum filtration is carried out by single - stage vacuum filtration or multi - stage vacuum filtration; preferably, the multi - stage vacuum filtration is carried out as follows: subjecting the suspension to single - stage vacuum filtration to obtain a carbon cloth substrate; impregnating the carbon cloth substrate with PTFE emulsion and then carrying out secondary vacuum filtration; and then drying to obtain the carbon cloth.
7. The CO2RR formic acid production system according to claim 2, wherein The mixture is prepared by first stirring the raw materials in an ice-water bath once and then stirring them at room temperature a second time; preferably, the rotation speeds of the first stirring and the second stirring are independently 1000 - 3000 rpm, such as 2000 rpm; the time of the first stirring is preferably 20 - 40 min, such as 30 min; the time of the second stirring is preferably 0.5 - 1.5 h, such as 1 h; and / or, the holding temperature of the stirring and heating is 80 - 90 °C, such as 85 °C; and / or, the stirring speed of the stirring and heating is 2000 - 4000 rpm, such as 2000 rpm or 3000 rpm; and / or, the stirring time of the stirring and heating is 0.5 - 1.5 h, such as 1 h; and / or, the temperature of the hot pressing treatment is 70 - 90 °C, such as 80 °C; and / or, the pressure of the hot pressing treatment is 1.5 - 3 ton, such as 2 ton; and / or, the time of the hot pressing treatment is 5 - 15 min, such as 10 min; and / or, after the hot pressing treatment, the thickness of the material is 0.5 - 1.5 mm, such as 1.0 mm; and / or, after the forming treatment, the thickness of the electrode film is 200 - 400 μm, such as 300 μm; and / or, the forming treatment is carried out by thinning with a rolling press; preferably, it is carried out by gradually thinning, and drying is carried out after each thinning; for example, first thin to 500 μm, then thin to 300 μm, and heat at 80 °C for 15 min after each thinning; and / or, the temperature of the second hot pressing is 80 - 150 °C, such as 100 °C; and / or, the pressure of the second hot pressing is 0.1 - 2 ton, such as 2 ton; and / or, the time of the second hot pressing is 10 - 60 min, such as 30 min.
8. A method for preparing formic acid, characterized in that, It is prepared by using the CO2RR formic acid production system according to any one of claims 1 - 7; Preferably, an intermittent electrolysis control method is used to apply current to the CO2RR formic acid production system, and the intermittent electrolysis control method is to set a power-off time during continuous operation; Preferably, the flow rate of the anode electrolyte flowing into the anode chamber is 0.5-1 mL·min -1 , for example, 0.85 mL·min -1 ; Preferably, the flow rate of CO2 introduced from the CO2 gas storage tank into the cathode chamber is 100 - 300 mL·min -1 , for example, 200 mL·min -1 .
9. The method for producing formic acid according to claim 8, characterized in that, The intermittent electrolysis control method is to power off after continuously operating for 1 - 5 h, such as 2 h or 4 h; and / or, the power-off time for each time of the intermittent electrolysis control method is 15 - 45 min, such as 20 min or 30 min; And / or, the current value of the applied current is 150 - 250 mA / cm 2 , such as 200 mA / cm 2 ; and / or, the intermittent electrolysis control method is to power off for 15 - 45 min after continuously operating for 1 - 5 h. Preferably, power off for 20 min after continuously operating for 2 h or power off for 30 min after continuously operating for 4 h.
10. The method for preparing formic acid according to claim 8, characterized in that, The intermittent electrolysis control method is used to apply current to the CO2RR formic acid production system; When a current is applied, the anolyte provides H to the cathodic chamber through the cation exchange membrane. + ; Gaseous CO2 is introduced into the cathodic chamber. Under the catalysis of the cathode catalyst, the electrolysis reaction generates products formic acid, CO, H2, and unreacted CO2. After the products formic acid, CO, H2, and unreacted CO2 enter the gas-liquid separator for separation, the separated liquid is formic acid; the gas is CO, H2, and unreacted CO2, which enters the burner after separation; at the same time, O2 is produced in the anodic chamber and enters the burner; CO, H2, and O2 burn in the burner, and the generated CO2 and H2O are recycled to the cathodic chamber for use as raw materials.